Effect of Experience of Internal Medicine Residents during Infectious Disease Elective on Future Infectious Disease Fellowship Application. (4th October 2017) - Blyth, Dana M; Barsoumian, Alice; Yun, Heather
Abstract: Background: Over 55% of trainees change career plans at least once during residency, but the factors that drive these decisions are undefined. Since 2008 at our institution, internal medicine (IM) residents have been required to do a four-week inpatient ID rotation as an intern. Timing of this rotation was randomly assigned. We evaluated the effect of IM interns' experiences on their ID rotation on future application for ID fellowship. Methods: Categorical IM interns rotating at Brooke Army Medical Center between July 2008 and June 2015 were included. Interns were grouped by eventual application to ID fellowship (IDA) and non-application (non-IDA). A review of schedules for the interns, faculty, and fellows was completed. Consult types seen during the interns' electives as tracked by fellow case logs were categorized into 18 topics by two ID staff. Up to two different categories could be coded for each consult. Data on trainee/fellow/faculty gender, branch of service, and years of experience, were obtained. Results: Between July 2008 and June 2015, 143 IM interns rotated through ID. Ten (7%) were IDA. Gender, military branch of service, year, and number of co-rotating trainees didn't affect future fellowship application. However, 90% of IDA compared with 46% of non-IDA rotated in block 1–7 (June-January) ( P < 0.01). IDA was not associated with rotating with program leadership or with the level of experience of fellows or faculty. There was a median of 34 and 33 consults seen during the rotation of IDA and non-IDA respectively. A median of 8 skin and skin structure infection consults were seen during months with IDA compared with 5 by non-IDA ( P = 0.02). There was also a trend towards more BSI and CNS infections seen during rotations with IDA ( P < 0.1). Otherwise there was no difference in consult types seen during their rotation. Conclusion: During a seven-year period when all interns were required to rotate on ID, there were minimal differences in consult type on the ID rotation amongst IDA and non-IDA. However, those randomly assigned to rotate on ID in the first six months of their intern year were more likely to become future ID applicants. This supports prior self-reported survey studies that early exposure to the field of ID may impact future career choice. Disclosures: H. Yun, American Board of Internal Medicine, Infectious Disease Board: Board Member, travel reimbursement, honorarium